Rejuvenating Financial Penalties: Using the Tax System to Collect Fines - Arie Freiberg
The current system for the imposition and collection of fines in Australia is significantly flawed. Fines are often inappropriately imposed or not imposed, inequitable, have high default rates and are expensive to enforce. This paper suggests an alternative scheme for the enforcement and collection of fines, a Fine Enforcement Collection Scheme (FECS). It is based on the principles underlying the Higher Education Contribution Scheme, which involves the proposition that fines may be paid depending upon an offender's future income. Though requiring a substantial re-casting of federal/state legal arrangements and an extension of the role of the Australian Taxation Office, the paper argues that such a scheme would increase the appropriate use of fines, be more equitable, improve collection rates and thus revenue to the imposing authorities. Concomitantly FECS has the high potential to enhance the credibility of the criminal justice system overall. If successful, this scheme could be expanded to help enforce a wider range of monetary sanctions.